The turning point in China's economic development - Garnaut, Ross; Song, Ligang (ANU E Press and Asia Pacific Press, 2006)
"The book discusses these important issues by focusing on China's long-term pattern of growth and employment, demographic shifts and rural-urban migration, its agricultural trade and local elections, China's banking sector reform and its fiscal sustainability, China's interaction with the international economy and global imbalances, its industrialisation and its resource and energy demand, was well as its environmental concerns."--Publisher's description